Facile fabrication of robust, recyclable, and multifunctional composite hydrogel sensor with MXene and cellulose microcrystals - Hasan, Md. Zahid; Xu, Chuanghua; Luo, Lei; Motaleb, K.Z.M. Abdul; Ahmed, Md Foysal; Tan, Sirui; Bashar, M.Mahbubul; Janutėnienė, Jolanta; Yue, Chengfei; Tu, Hu; Sha, Sha; Cai, Guangming; et al. (Industrial crops and products, 2025)
Conductive hydrogel has garnered significant fascination for its potential as wearable sensor. However, designing a wearable sensor with excellent electrical conductivity, self-healing capability, mechanical strength and recyclability is still difficult to accomplish. Herein, a multifunctional composite hydrogel was fabricated via a one-pot method with cellulose microcrystals (CMCs) and MXene. The introduction of CMCs to the hydrogel composite provided mechanical strength and assisted in homogeneous distribution of MXene resulting the high electrical conductivity. The subsequently prepared conductive composite hydrogel exhibited improved tensile strength (87.4 kPa) and elongation at break (424 %) with optimum composition, outstanding electrical conductivity (1.11 S/cm) and quick electrical self-healing efficiency without external stimuli. The temperature responsiveness of the conductive composite hydrogel was mainly accredited for reducing interfacial thermal resistance ensuing of continuous heat conduction pathways. It also demonstrated the notable fire resistance offering quick fire-warning signals within ∼1 sec. The developed conductive composite hydrogel could monitor subtle human movements efficiently as well as possessed the ability to track human body temperature, indicating effective means of electronic skin (E-skin) for smartphone interfacing. This work introduces a feasible approach in designing an electrically conductive, biodegradable wearable composite hydrogel with potential applications as versatile motion, temperature and fire sensor. [Display omitted] •Praperation of a multifunctional hydrogel sensor with cellulose microcrystals and MXene.•Highly sensitive sensing capabilities for strain, temperature, and fire.•Simultaneously exhibiting good recyclability and biodegradability.